Teoretycznoprawne aspekty przedstawicielstwa podmiotów prywatnych: [Theoretical and legal aspects of the representation of private entities] (Studia Prawnicze / The Legal Studies, 2013)
The institution of representation is of enormous theoretical and practical significance for contemporary legal sphere: it facilitates and accelerates legally binding activities, enabling participation of persons who, for various reasons, cannot validly undertake legal acts themselves. In the continental Europe, the construction of representation originates from the Roman law, which inspired the German law (Stellvertretung), which in turn considerably influenced contemporary legal systems in various countries, including the Polish law. Comparison of the construction of representation in the Polish law with the objectives, tasks and functions of representation in the German law will demonstrate characteristic features of the Polish legal regulation and influence of the German law thereupon. In addition, it will demonstrate that the German construction of representation is based on Zurechnung mechanism, while the Polish construction refers to legal fiction.